The Effect of Pursed-Lip Breathing on Functional Capacity of Stable Chronic Obstructive Pulmonary Disease Patient Assessed by Six Minutes Walk Test - Dimas Hudy Ariadie; Sumardi Sumardi; Herni Retnowulan (Faculty of Medicine Universitas Gadjah Mada, 2020)
Background. The number of people with Chronic Obstructive Pulmonary Disease (COPD) in Indonesia isestimated to continue grow and currently has reached 4.8 million sufferers resulting in a large socio-economic burden. Management of COPD requires a comprehensive approach involving rehabilitation activities such as Pursed Lip Breathing (PLB) in order to increase the functional capacity of sufferers. Assessment of physical functional capacity of COPD patients can be evaluated through the Six Minute Walk Test / 6-minutes walk test, which can also assess changes in post-intervention functional capacity such as pulmonary rehabilitationprograms.Aims. This study aimed to determine the effect of pulmonary rehabilitation with PLB technique for 4 weeks on the achievement of distance through a six-minute road test in COPD patients who received standard therapy.Methods. An experimental, Randomized Controlled Trial (RCT) study was conducted on stable COPD patients with classification of Global Initiative for Chronic Obstructive Lung Disease stage II (GOLD 2) and GOLD 3 ( Stage III). The study was conducted at the Rumah Sakit Khusus Paru (RSKP) Respira Bantul, Yogyakarta. Subjects were taken randomly as a treatment Pursed Lips Breathing (PLB) or control group. The treatment group consisted of 38 subjects, doing PLB 8 minutes for 28 days (4 weeks) in a row. The placebo group consisted of 37 subjects only continuing the previous standard therapy. Six-minute walking test measurements were carried out in both groups before and after treatment and compared between the PLB and control groups. The difference in average delta range between groups that received PLB and controls was tested by unpaired t-test.Results. There was a difference increase in the average delta range of the six-minute walk test which was not significant between the two study groups. The increase delta mean range in the six-minute walk test treatment group was greater (22.19 ± 45.54 meters) compared to the control group (18.54 ± 42.57 m), with a P = 0.720.Conclusion. There was an improvement in functional capacity in the form of increased performance distance in the six-minute walk test for COPD patients who received standard therapy and pulmonary rehabilitation by pursed-lip breathing (PLB) technique.